COMUNICACIÓN INTERPERSONAL EN MATRIMONIOS DE DOBLE INGRESO: RETOS Y ESTRATEGIAS DE LAS MUJERES MEXICANAS PARA COMUNICARSE CON SU PAREJA 1 - Ma. Eugenia GONZALEZ ALFITA (Fonseca, Journal of Communication, 2023)
With a focus on work-family balance, this exploratory study focused on finding the communication and consider what strategies women use to solve them. Also explore the nature of the main issues on which the couple talks about.